Divergent trends of urban thermal environmental characteristics in China. (10th March 2021) - Zheng, Yuhan; Huang, Lin; Zhai, Jun
Abstract: Due to the rapid urbanization in China, urban expansion has gradually shifted from large cities to small cities, causing spatiotemporal changes in the urban thermal environment. The differential thermal environmental characteristics of 334 cities at different hierarchy caused by urbanization are investigated in this study. Then, the spatiotemporal changes of land surface temperature (LST), albedo, and emissivity among urban areas and their surrounding buffer areas are analyzed during 2000–2015. We found that the urban warming effect is usually prominent in the daytime, with an obvious seasonal differentiation between 0.32 °C[0.27, 0.38] in summer and -0.14 °C[-0.20, -0.07] in winter. The nighttime warming effect during summer resembles that in winter, in the range 0.23–0.25 °C. In addition, the number of cities with intensifying trends of the warming effect in summer daytime account for 50% of the total cities, but only 9% in winter nighttime, 23% in summer nighttime, and 25% in winter daytime. Large cities usually have obvious warming effects compared with small cities. But the highest warming effect is found in megacities during the daytime and in medium cities during the nighttime. In southern subtropical cities, the warming of urban zones is high in the daytime and low in the nighttime, while it is opposite in arid and semiarid regions, especially in winter. The negative correlations between the difference of surface albedo (emissivity) and LST in megacities and metropolitan areas emphasize that nighttime warming primarily results from radiation absorption and release affected by urbanization. This study may advance the understanding of the heterogeneity in the warming effects of different cities in China and support policy formulation and regulation to adapt to urban warming.